2002
DOI: 10.1038/sj.eye.6700065
|View full text |Cite
|
Sign up to set email alerts
|

Keratocyte apoptosis and corneal antioxidant enzyme activities after refractive corneal surgery

Abstract: and corneal antioxidant enzyme activities after refractive corneal surgery AbstractPurpose Refractive corneal surgery induces keratocyte apoptosis and generates reactive oxygen radicals (ROS) in the cornea. The purpose of the present study is to evaluate the correlation between keratocyte apoptosis and corneal antioxidant enzyme activities after different refractive surgical procedures in rabbits. Methods Rabbits were divided into six groups. All groups were compared with the control group (Group 1), after epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Physical abrasion, following on from reduced tearing, stimulates the cells in the conjunctival epithelium to produce various cytokines (IL-1, IL-6, IL-8 and TNF-α) which then flow inside a tear film relatively deprived of protection factors, such as EGF and retinol. This stimulates apoptosis of the keratocytes [33,35], which is also stimulated by the release of reactive oxygen species induced by surgery on the cornea [3]. Apoptosis is of course the first essential step of epithelial healing [34], but it may also be a contributing factor in the frequent occurrence of a reduction in refraction or post-operative haze [19,28].…”
Section: Introductionmentioning
confidence: 99%
“…Physical abrasion, following on from reduced tearing, stimulates the cells in the conjunctival epithelium to produce various cytokines (IL-1, IL-6, IL-8 and TNF-α) which then flow inside a tear film relatively deprived of protection factors, such as EGF and retinol. This stimulates apoptosis of the keratocytes [33,35], which is also stimulated by the release of reactive oxygen species induced by surgery on the cornea [3]. Apoptosis is of course the first essential step of epithelial healing [34], but it may also be a contributing factor in the frequent occurrence of a reduction in refraction or post-operative haze [19,28].…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen-free-radical-induced tissue damage after PRK is well documented [9,10,11,12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…The lipid peroxidation in the superficial corneal stroma is generated by oxygen free radicals, and it induces alterations in cellular proteins and membranes. This type of acute injury is responsible in part for corneal haze because of the apoptosis of keratocytes [26,27] . Many studies have revealed that excimer laser UV radiation decreases the detoxifying activity of the glutathione peroxidase enzyme, which is the main component of the corneal antioxidant system [28,29] .…”
Section: Introductionmentioning
confidence: 99%